IMPLEMENTING TASK-BASED LANGUAGE TEACHING TO OVERCOME THE PROBLEMS OF TEACHING SPEAKING - SUSWATI HENDRIANI (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2014)
Teaching students to speak English is not an easy task. The teachers shoud consider and think hard about several points to be done: to make the students motivated to speak English, to keepthem speaking the new language, and to make them have accuracy in speaking the language, and to correct the students’ mistakes without feeling being blamed or discouraged. To handle the difficult tasks previously mentioned, the English teachers should find a solution. Teaching the students through unforgettable, interesting experiences might be one of the solutions that they can choose. Therefore, teaching speaking might be best done through task-based instruction. Kata kunci: teaching, speaking